Application of Trojan Horse Method to radioactive ion beams induced reactions. (September 2020) - Gulino, Marisa; Cherubini, Silvio; Kubono, Shigeru; Lamia, Livio; Cognata, Marco La; Pizzone, Rosario Gianluca; Yamaguchi, Hidetoshi; Hayakawa, Seya; Wakabayashi, Yasuo; Iwasa, Naohito; Kato, Seigo; Komatsubara, Tetsuro; et al.
Abstract: In the last decades, many indirect methods have been developed to measure the cross section of nuclear reactions at the low energies interesting in many astrophysical scenarios. The Trojan Horse Method uses a three body reaction, involving by a strong clusterized nucleus, to infer information about a two body reaction of interest, selecting the events that proceed through the quasi-free reaction mechanism. To reconstruct the reaction kinematic and to identify the useful reaction mechanism, the energy and angle of at least two of the three outgoing particles must be carefully measured. Moreover, enough statistics is required, as the quasi-free events usually represent just a small fraction of the acquired statistic. These requirements hardly match with the typical characteristics of radioactive ion beams: low intensity, large divergence and possible presence of contaminants. For this reason, only recently the Trojan Horse Method has been applied to study reactions induced by radioactive beams. This application gives also the opportunity to measure cross section of neutron induced reactions on radioactive isotopes, even if they have a short lifetime. In the following some results obtained in the study of the reactions 18 F( p, α ) 15 O and 18 F( n, α ) 15 N will be presented.